Pengembangan Media Pembelajaran Multimedia Interaktif Berbasis Flash untuk Meningkatkan Hasil Belajar Mahasiswa - Novi Marlena; Renny Dwijayanti; Muhammad Edwar (Faculty of Economics, State University of Jakarta., 2018)
This type of research is the development of research. Development using a modification model Borg and Gall (2003), the data collection techniques through technical documentation and questionnaires. Data analysis techniques were the data results of the review and testing of the products as the basis for improvement of media. Than, questionnaire respondents assessment of the effectiveness of media related learning on student results. From the overall stages of the study showed that there are significant differences in student learning outcomes by using powerpoint compared with the results of classical learning of students by using interactive media flash